VOTRAGE study: Phase I dose-escalation study of pazopanib in unfit older patients. Issue 5 (June 2021) - Mourey, Loïc; Le Louedec, Félicien; Ravaud, Alain; Paludetto, Marie-Noëlle; Digue, Laurence; Gomez-Roca, Carlos Alberto; Valentin, Thibaud; Balardy, Laurent; Olivier, Pascale; Cabarrou, Bastien; Filleron, Thomas; Chatelut, Etienne
Abstract: Background: Pazopanib is a tyrosine kinase inhibitor given at the approved dose of 800 mg orally once daily (OD), but often requiring individual dose adjustment due to toxicity. Limited data is available to guide prescription in older patients especially the unfit according to geriatric assessment. Patients and methods: VOTRAGE is a 3 + 3 dose-escalation, open-label phase I trial of continuous OD oral administration of pazopanib to evaluate safety, PK and PD data in unfit older patients with advanced solid tumors. The primary objective was to determine the maximum tolerated dose (MTD). PK data were compared with those obtained in younger adult patients in a population PK analysis. Results: Eighteen patients with a median age of 82.5 years (range 75–91) were included in three dosing cohorts (400, 600, and 800 mg daily). Three dose-limiting toxicities (DLT) were observed in five patients at 800 mg and one DLT at 600 mg in six evaluable patients. MTD was defined as level 2 dose (600 mg). Individual oral clearance was not correlated with age. A relationship was observed between the occurrence of DLT and pazopanib plasma exposure. Decreased oral bioavailability of pazopanib when given with proton-pump inhibitors was confirmed in this group of patients. Conclusion: We recommend performing geriatric assessment in patients older than 75 and starting pazopanib at 600 mg per day in unfit older patients. Therapeutic drug monitoring appears very helpful in this population.